Peran Perilaku Keuangan Dalam Memediasi Pengaruh Literasi Keuangan dan Pendapatan Terhadap Keputusan Berinvestasi - Ilyas, Andre; Nuryati, Arnita; Suryadi, Dodi; Yeni, Fitri (Jurnal Akuntansi dan Keuangan, 2024)
This research aims to see whether financial literacy and income affect investment decisions with financial behavior as an intervening variable. The population in this study were 53 SMEs in the services sector in Kec. Padang Barat, Kota Padang. The sampling technique in this research was Nonprobability Sampling using Total Sampling with a total of 53 SMEs Services that are Actively Investing in Kec. Padang Barat, Kota Padang. Analysis of processing data used in SPSS 23. The results of this study are financial literacy has a negative and not significant effect on financial behavior, income has a positive effect on financial behavior, financial literacy has a negative effect on investment decisions, income and financial behavior have a positive effect on investment decisions. Furthermore, financial literacy and income has a negative effect on investment decisions through financial behavior.